PENGARUH KOMPENSASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS PENGELOLAAN SUMBER DAYA AIR DI KABUPATEN SIDENRENG RAPPANG - Sudarmi Sudarmi (IAIN Manado, 2017)
AbstractThis study was conducted to answer the problem Whether compensation in the form of salaries and allowances partially positive and significant impact on the productivity of employees working at the Department of Water Resources Management Sidenreng Rappang? Thus, this study aims to determine Is the compensation in the form of salaries and allowances partially positive and significant impact on the productivity of employees working at the Department of Water Resources Management Sidenreng Rappang. for that, the results of this study would be useful : (1) as inputs to the leadership at the Department of Water Resources Management Sidenreng Rappang in the development of good quality officials related to the quality and skills of employees, (2) for the development of knowledge about the development of civil servants (PNS) and (3) as a reference. This study is a verification that is correlational, meaning that the data and facts collected from the field is not manipulated, just to test the theory as well as to validate the hypothesis, with a sample size of 30 people. Data collection techniques used were questionnaires, observations, and interviews.Analysis of the data used is ; Descriptive statistical analysis and statistical analysis infrensial. In analyzing the data using SPSS 18 software.The results showed:1. Compensation is in both categories. It is in terms of; (1) salary, (2) incentives, (3) life and health insurance, and (4) housing2. Productivity of employees working in the category both in terms of ; (1) conduct a constructive, (2) trust yourself, (3) responsible, (4) a love of work, (5) have the foresight, (6) Overcoming the problem, (7) had a positive contribution, and (8) have the power.3. The results of the calculation of F test obtained F arithmetic 14.191 and F table (0.05 : 1 : 30) amounted to 4, 17 or the value of F larger than F table. Therefore Fo > Fi, your Hi accepted, which means there is a variable dependent nature of work productivity with compensation, or it can be said that the hypothesis in this research is received from the analysis SPSS.18 (see Table Cooeficient) turned out to be significant to the variable compensation is far below 0,001 0.05, therefore H1 = significant regression coefficient so that compensation effect on employee productivity. Keywords : Compensation and Working produtivitas